Rapid mobilization of a virtual pediatric chronic pain clinic in Canada during the COVID-19 pandemic. Issue 1 (1st January 2020) - D'Alessandro, Lisa N.; Brown, Stephen C.; Campbell, Fiona; Ruskin, Danielle; Mesaroli, Giulia; Makkar, Mallika; Stinson, Jennifer N.
ABSTRACT: Background: Studies have been conducted describing the potential for using virtual care software during disasters and public health emergencies. However, limited data exist on ways in which the Canadian health care system utilizes virtual care during disasters or public health emergencies. Aims: Due to the need for social distancing and reduction of nonessential ambulatory services during the COVID-19 pandemic, the SickKids Chronic Pain Clinic sought to transition care delivery from in person to virtual. The virtual clinic aimed to reduce risks associated with physical contact and environmental exposure without reducing access to care itself. Methods: Harnessing of various digital tools including Ontario Telemedicine Network Guestlink, Zoom, and Microsoft Teams. The Chronic Pain Clinic Team worked together to communicate with patients and families, schedule virtual visits, establish remote access to clinical data collection tools, digitize the after-visit summary, and add resources on pain self-management to the clinic's website. Results: The Chronic Pain Clinic successfully transitioned all clinic appointments (multidisciplinary and individual; 77 appointments) over a 2-week period to virtual care. Virtual clinics did not surpass the usual time taken pre-COVID-19, suggesting that the clinic workflow was readily adaptable to virtual care. Conclusions: Access to quality virtual care is essential to prevent chronic pain from taking a toll on the lives of patients and families. Rapid establishment of a virtual clinic without gaps in service delivery to patients is possible given institutional support and a team culture centered around collaboration and flexibility.